2012
DOI: 10.4414/smw.2012.13548
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of serotonin in liver regeneration

Abstract: Serotonin has a multifunctional role in many different organs serving either as a neurotransmitter in the central nervous system or a paracrine factor in the gastrointestinal tract. Over 90% of serotonin is synthesised in the enterochromaffin cells of the intestine and subsequently taken up by platelets. The involvement of platelet-derived serotonin in liver mass restoration after partial hepatectomy or toxic injury has been greatly investigated during the last decade. There is a growing body of evidence impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 57 publications
0
26
0
2
Order By: Relevance
“…Several lines of evidence suggest a role for serotonin in the regulation of energy balance, specifically in relation to glucose and fatty acid metabolism. Serotonin is known to induce hepatic regeneration (Lesurtel et al 2006), glucose secretion from the liver, and insulin secretion by the pancreas (Sugimoto et al 1990, Watanabe et al 2011 as well as liver glucose uptake mechanisms (Moore et al 2004(Moore et al , 2005 and glycogen metabolism (Papadimas et al 2012). Furthermore, serotonin has been shown to regulate glucose-stimulated insulin secretion by the b cells of the pancreas during pregnancy, and it is critical for glucosestimulated insulin secretion in an insulin-resistant state (Ohara-Imaizumi et al 2013, Kim et al 2015.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several lines of evidence suggest a role for serotonin in the regulation of energy balance, specifically in relation to glucose and fatty acid metabolism. Serotonin is known to induce hepatic regeneration (Lesurtel et al 2006), glucose secretion from the liver, and insulin secretion by the pancreas (Sugimoto et al 1990, Watanabe et al 2011 as well as liver glucose uptake mechanisms (Moore et al 2004(Moore et al , 2005 and glycogen metabolism (Papadimas et al 2012). Furthermore, serotonin has been shown to regulate glucose-stimulated insulin secretion by the b cells of the pancreas during pregnancy, and it is critical for glucosestimulated insulin secretion in an insulin-resistant state (Ohara-Imaizumi et al 2013, Kim et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin is thought to mediate hepatic regeneration (Lesurtel et al 2006) as well as glucose and insulin secretion (Sugimoto et al 1990). Studies have shown that serotonin is involved in liver glucose uptake mechanisms (Moore et al 2005) and glycogen metabolism (Papadimas et al 2012). Additionally, serotonin has been shown to be increased in mice that are subjected to fasting conditions, which results in the stimulation of lipolysis and liver gluconeogenesis via the serotonin receptor 2b subtype in adipocytes and hepatocytes (Sumara et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Слід відзначити, що із семи родин серотонінових рецепторів у різних клітинних популяціях печінки найбільш інтенсивно експресуються 5-НТ 2 -рецепто-ри, які опосередковують вплив аутокоїда на метаболічні та регенеративні процеси в тканині цього органа [6][7][8][9]. Нині більшість досліджень гепатотропних ефектів серото-ніну спрямовані на з'ясування його дії на регенерацію і канцерогенез у печінковій тканині [10]. Однак питання впливу цього бі-огенного аміну на секрецію жовчі, як одного із показників, що відображає функціональний стан печінки, є недостатньо вивченим.…”
Section: вступunclassified
“…Then when needed, serotonin is transported and released at sites of injury [10]. Although initially related to liver fibrosis, other studies have implicated the release of serotonin by platelets as a mediator of liver regeneration and repair after partial hepatectomy [9,11,12]. These opposite observations let us with a plethora of unanswered questions that we aim to address in this article.…”
Section: Introductionmentioning
confidence: 99%